2018
DOI: 10.1590/0102.3772e3426
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Using HJ-Biplot Analysis in Executive Functions Studies

Abstract: Executive functions (EFs) are considered a multiple system of processing, associated with different components, such as inhibition, working memory, planning, among others. The study of EFs requires the assessment of all its components, having in mind the socio-demographic and cognitive characteristics of the target population. Nowadays, analysis of variance is used to achieve this goal; nevertheless, HJ-Biplot analysis overcome its limitations by allowing simultaneous examination of multiple data, such as thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this study we used HJ-Biplot to visualize the data which has many advantages. (1) It allows the simultaneous examination of multiple variables in the same graphical representational plane (2) It allows to compare on an individual and group level (3) It identifies the provision of information on the relationship between measures of the same and/or different origin; (4) There is no need to perform a posteriori contrasts (Ruiz et al, 2018). However, it is difficult for the user to know which points (variables) are driving the solution and thus should be used to interpret the results.…”
Section: Compositional Data Analysis (Cda)mentioning
confidence: 99%
“…In this study we used HJ-Biplot to visualize the data which has many advantages. (1) It allows the simultaneous examination of multiple variables in the same graphical representational plane (2) It allows to compare on an individual and group level (3) It identifies the provision of information on the relationship between measures of the same and/or different origin; (4) There is no need to perform a posteriori contrasts (Ruiz et al, 2018). However, it is difficult for the user to know which points (variables) are driving the solution and thus should be used to interpret the results.…”
Section: Compositional Data Analysis (Cda)mentioning
confidence: 99%
“…A more exhaustive review of HJ-Biplot applications can be found in Nieto 2014 11 . Some recent applications of the HJ-Biplot method are found in Serafim 2013 10 ; Gallego-Álvarez 2015 12 ; Delgado-Álvarez 2015 13 ; Patino-Alonso 2015 14 ; Hernández-Suárez 2016 15 ; Ruiz 2018 16 ; Oliveira-Da Silva 2019 17 ; and Jaramillo-Feijoo 2020 18 .…”
Section: For Projections Of Row Markers Onto Column Markersmentioning
confidence: 99%
“…Thus, its use has increased over the last 20 years in multiple fields (food industry, health, and social sciences) because HJ-Biplot provides options for evaluating associations between multiple observations and variables, with fewer restrictions than conventional methods, and the advantage of being specifically designed for the inspection of data matrices (Martínez-Regalado et al, 2021). Ruiz et al (2018) highlighted four main advantages: a simultaneous examination of multiple variables in the same graphical representational plane; different comparisons at individual and group levels; the relationship between measures of the same and/or different origins; and no need to perform a posteriori contrast.…”
Section: Introductionmentioning
confidence: 99%